Принципи правоохоронної діяльності відповідно до Європейської конвенції з прав людини та практики Європейського суду з прав людини - Мармазов, В.С. (Часопис Київського університету права, 2009)
В статье раскрываются основные принципы правоохранительной деятельности в соответствии с Европейской конвенцией прав человека и закрепленные в практике Европейского суда по правам человека и рекомендациях Комитета Министров Совета Европы, дан обзор практики Европейского суда по правам человека в этой области. Basic principles of law-enforcement activity are being opened up in the article according to European convention of human rights and has been fastened in practice of the European court on human rights and recommendations of Committee of Ministers of Council of Europe, the review of practice of the European court on human rights according to the sphere mentioned above has been given.